Isolasi dan Pemurnian DNA Genomik dari Sampel Darah Manusia Menggunakan Metode Spin Column - Nuri Febriani; fadilaturahmah fadilaturahmah; Desi Arisanty (GLOBAL SCIENTS PUBLISHER, 2026)
Genomic DNA isolation is a crucial step in various molecular biology analyses because the quality of the DNA obtained is crucial for the success of subsequent analyses. This study aims to describe the process of isolating and purifying genomic DNA from human blood samples using the spin column method and to evaluate the quality of the resulting DNA. The study was conducted at the Biomedical Laboratory, Faculty of Medicine, Andalas University, Padang, West Sumatra. The isolation process was carried out using a silica column-based DNA extraction kit, which includes the stages of cell lysis, DNA binding to a silica membrane, washing, and elution. The quality of the extracted DNA was evaluated based on its concentration and absorbance ratio A260/A280 using a microvolume spectrophotometer. The results showed that most samples had an A260/A280 ratio in the range of 1.80–1.90, indicating DNA with a good level of purity and relatively free from protein contamination. The obtained DNA concentration varied between 1.4–92.2 ng/µl, reflecting differences in extraction efficiency in each sample. The spin column method has proven effective in producing genomic DNA with adequate quality and purity for advanced molecular biology applications, such as PCR, electrophoresis, and sequencing. With its fast, safe, and reproducible procedure, this method has become one of the most widely used techniques in diagnostic laboratories and molecular research.